Strategi Komunikasi Bisnis dalam Sistem Perekrutan Prospek Multi-Level Marketing Tiens di Kota Cimahi - Fadila Fujiyanti; Detya Wiryany; Wawan Darmawan (ArtComm, 2024)
This research focuses on the Sharia-compliant Multi-level Marketing (MLM) business of Tiens in Cimahi, which has obtained halal certification from BPOM in 100 countries and is maintained by the Sharia Council of the Indonesian Ulema Council (DSN-MUI). The study explores the implementation, recruitment issues, and communication strategies within this MLM business, considering the perspective of Islamic business ethics. A qualitative method is employed in this research as the information gathered from interviews is recorded and used to explain a particular phenomenon or issue. The findings indicate that the marketing strategy of Tiens Sharia MLM revolves around recruiting new members to sell products. New distributors purchase membership packages and starter kits to begin. The implementation of this MLM is carried out through regular meetings, seminars, and product introduction events. However, there is public debate regarding the halal status and legitimacy of this business. Overall, this research provides insights into the implementation of Tiens Sharia MLM, emerging ethical issues, and the societal debate surrounding this business. Awareness of sustainability and transparency in MLM operations emerges as key factors in building sustainable relationships with members and the community.